(untitled) (Construction Economics and Building, 2022)
Organisational internal risk factors, which include management, material, finance, and design risk factors, affect oil and gas construction projects’ success in emerging nations, in which Malaysia is no exception. The purpose of this study is to examine the effect of these internal risk factors and government support on oil and gas projects among sixty-one (61) employees of oil and gas firms using a questionnaire survey. The data collected were analysed using structural equation modelling (SEM) techniques. The results revealed that all the exogenous variables (design risk, management risk, financial risk and material risk factors and government support) significantly impact project success. According to the findings, all exogenous variables (design risk, management risk, financial risk, material risk factors, and government support) have substantial effects on project success. The study developed an all-inclusive framework that can assist stakeholders in the industry in mitigating internal risk factors in ensuring the success of projects. Policy implications and future study paths are considered.